Design, Development and Evaluation of Oral Dissolving film of Montelukast Sodium - Chauhan, Manhi; Sharma, Ashutosh; Sharma, Priya; Sain, Sunil (Journal of Biomedical and Pharmaceutical Research, 2024)
Montelukast Sodium (MS) is widely used for managing asthma and allergic rhinitis due to its leukotriene receptor antagonist properties. However, traditional oral dosage forms often lead to challenges in patient compliance and delayed onset of action. This study focuses on the design, development, and optimization of oral dissolving films (ODFs) of Montelukast Sodium, aimed at improving patient compliance and ensuring rapid drug release. Using the solvent casting method, various formulations were prepared with different concentrations of hydroxypropyl methylcellulose (HPMC), Eudragit, and Xanthum Gum and plasticizers like polyethylene glycol (PEG). The films were evaluated for their thickness, drug content uniformity, disintegration time, in vitro dissolution, and mechanical properties. The optimized ODFs F5 demonstrated rapid disintegration (10 seconds) and high drug release (99.99% within 5 minutes), indicating their potential to enhance therapeutic efficacy and patient adherence. Keywords: HPMC, Eudragit, Xanthum Gum, PEG, Film.